Association between morphological traits and yield components in the durra sorghums of Ethiopia - Tesso, Tesfaye T.; Tirfessa, Alemu; Mohammed, Hussein (My University, 2011)
The Ethio-Sudan region is recognized as the center of origin and diversity for cultivated sorghum. All major races of the crop are widely grown in Ethiopia with durras being dominant. The objective of the present study was to determine the extent of morphological variability among the Ethiopian durras and examine the pattern of relationships among these traits and their association with yield and yield components. Two hundred accessions collected from major sorghum-growing regions of the country were evaluated during the 2007 season at two locations representing hot and dry low land and mild mid-altitude environments. A randomized complete block design with three replications was used. Data were collected on phenology, plant height, a range of leaf traits and yield components. Significant variation was observed among all traits measured. Phenological traits and plant height were significantly correlated with each other and with all leaf traits. There was positive correlation among leaf traits, and between leaf traits and yield components except thousand kernel weight (TKW) and panicle length (PL). Grain fi ll duration was negatively correlated with all traits except days to maturity, TKW, and leaf length. Yield components except PL and TKW were positively correlated with each other. Selection that focuses on key yield components, larger leaf area, and on enhancing the grain filling rate by reducing excessive grain fill duration may contribute to yield improvement.
Citation: Tesso, Tesfaye, Alemu Tirfessa, and Hussein Mohammed. “Association between Morphological Traits and Yield Components in the Durra Sorghums of Ethiopia.” Hereditas 148, no. 3 (2011): 98–109. https://doi.org/10.1111/j.1601-5223.2011.02229.x.
Keywords: Durra sorghum; Ethiopian durra sorghum; Morphological variability; Yield components